Semiconductor Materials : an Introduction to Basic Principles - Yacobi, B. G. (Microdevices, Physics and Fabrication Technologies., 2003)
The main objective of this book is to provide an introductory perspective of the basic principles of semiconductors, being an integrated overview of the basic properties, applications, and characterization of semiconductors in a single volume. This book is suitable for both undergraduate and graduate students, and for researchers, working in a wide variety of fields in physical and engineering sciences, who require an introductory and concise description of the field of semiconductors.